A cuboidal B2 nanoprecipitation-enhanced body-centered-cubic alloy Al0.7CoCrFe2Ni with prominent tensile properties. (15th July 2016) - Wang, Qing; Ma, Yue; Jiang, Beibei; Li, Xiaona; Shi, Yao; Dong, Chuang; Liaw, Peter K.
Abstract: The present work reports a cuboidal B2-coherently-enhanced body-centered-cubic (BCC) alloy Al0.7 CoCrFe2 Ni with prominent tensile properties at both room (ultimate tensile strength σ b = 1223 MPa and elongation to fracture δ = 7.9%) and high temperatures. This multi-principal-element alloy is developed out of a cluster formula [Al–M14 ]Al1 issued from the cluster-plus-glue-atom model of a BCC structure. Here, the [Al–M14 ] cluster is centered by Al, surrounded by fourteen average atoms M = Co1/5 Cr1/5 Fe2/5 Ni1/5, and glued with one Al atom. Its excellent mechanical properties are attributed to a superalloy-like microstructure, characterized by cuboidal B2 nanoprecipitates coherently embedded in the BCC matrix. Graphical abstract: